Free at last : a Juneteenth poem - Kincaid-Rolle, Sojourner (Sterling Children's Books, 2022)
"Deeply emotional, evocative free verse by poet and activist Sojourner Kincaid Rolle traces the solemnity and celebration of Juneteenth from its 1865 origins in Galveston, Texas to contemporary observances all over the United States. This is an ode to the strength of Black Americans and a call to remember and honor a holiday whose importance reverberates far beyond the borders of Texas"--